Top-down versus bottom-up: coupling both modelling approaches for a prospective study on biofuels - Costa R.C. da; Fallot A. (Comprehensive economic and spatial bio-energy modelling, 2002)
Since in the first and decisive stages of their development, bio-energy potentials are highly dependent on favourable public intervention and is ability to overcome the lock-in effects that maintain the hegemony of conventional fossil energies, bio-energy potentials should not only be queried in terms of costs and available volumes. Public support for a given bio-energy is ail the more legitimate when its future potential can be proved high. For that matter, prospective studies, which include both the techno-economic aspects of a given bio-energy and the economic conditions of its emergence and development, are required. The engineers' and the economists' points of view regarding technical change, must be combined into some hybrid bottom-up top-down models, allowing for the consistency of technological choices at the micro-level with some macro-economic aggregates, namely activity indicators. Central points to be considered are the possible feedback impacts of technological choices on the macro-economy via changes in the technical coefficient. The role of prices needs special attention in this matter. The hybrid model presented here has been used for a prospective study on bio-energies in Brazil and another on biofuels in France. It essentially consists of the iteratively linked projections of both the input-output table and the energy balance of the economy. We shall describe the modelling methodology, the main hypotheses and experts sayings the model relies on, and finally illustrate with some results on biofuels in Brazil.
Seminar on Comprehensive Economic and Spatial Bio-Energy Modelling, 2001/06/07-08, Grignon (France)